2011
DOI: 10.1073/pnas.1109843108
|View full text |Cite
|
Sign up to set email alerts
|

Different levels of the Tripartite motif protein, Anomalies in sensory axon patterning (Asap), regulate distinct axonal projections of Drosophila sensory neurons

Abstract: The axonal projection pattern of sensory neurons typically is regulated by environmental signals, but how different sensory afferents can establish distinct projections in the same environment remains largely unknown. Drosophila class IV dendrite arborization (C4da) sensory neurons project subtype-specific axonal branches in the ventral nerve cord, and we show that the Tripartite motif protein, Anomalies in sensory axon patterning (Asap) is a critical determinant of the axonal projection patterns of different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 35 publications
1
57
0
Order By: Relevance
“…Neogenin, which is closely related to DCC, is predicted to interact with TRIM9 (Meyerhardt et al, 1997;Morikawa et al, 2011). Netrin and neogenin are involved in dendritic selfavoidance in Drosophila melanogaster (Smith et al, 2012), which may be consistent with altered dendritic arborization observed in hippocampal neurons following netrin stimulation or Trim9 de- letion.…”
Section: A Possible Role For Netrin and Trim9 In Adult Neurogenesismentioning
confidence: 91%
See 3 more Smart Citations
“…Neogenin, which is closely related to DCC, is predicted to interact with TRIM9 (Meyerhardt et al, 1997;Morikawa et al, 2011). Netrin and neogenin are involved in dendritic selfavoidance in Drosophila melanogaster (Smith et al, 2012), which may be consistent with altered dendritic arborization observed in hippocampal neurons following netrin stimulation or Trim9 de- letion.…”
Section: A Possible Role For Netrin and Trim9 In Adult Neurogenesismentioning
confidence: 91%
“…Deletion of Trim9 increases hippocampal dendritic and axonal complexity in vitro TRIM9 regulates the branching and guidance of axons of developing murine cortical neurons (Winkle et al, 2014;Menon et al, 2015) and in invertebrates (Hao et al, 2010;Morikawa et al, 2011;Morf et al, 2013). TRIM9 is present in cultured hippocampal neurons, where its expression increases over time in vitro (Fig.…”
Section: Trim9 Interacts and Colocalizes With The Netrin-1 Receptor Dmentioning
confidence: 99%
See 2 more Smart Citations
“…For MARCM analysis, v'ada MARCM clones were generated and examined as described previously (Morikawa et al 2011). Females of hsFLP 122 , ppk-GAL4 UAS-mCD8GFP; tub-GAL80 FRT2A/TM6B were mated with males of the following genotypes: (1) trio E4.1 FRT2A/TM6B, (2) UAS-trio; trio E4.1 FRT2A/TM6B, and (3) yw, FRT2A.…”
Section: Drosophila Geneticsmentioning
confidence: 99%